Exploring a model nuclear planning and response program: Evaluating public awareness of written risk and emergency - Peters, PhD, Ekong J.; Hackerott, PhD, Caroline S.; Jia, PhD, Weijia (Journal of Emergency Management, 2021)
High-reliability organizations (HROs) including commercial airlines, the NASA Space Shuttle engineering team, US Naval aircraft carrier and nuclear submarine crews, and US nuclear power plants are relatively safe. However, these organizations experience system breakdowns often with catastrophic outcomes. This study focuses on risk information management strategies employed by a nuclear energy power plant located within 10 miles of a population center. The evacuation planning zone (EPZ) includes a hospital, several schools, and a public university. The nuclear plant provides written preparedness and evacuation information for all residents within the EPZ in the event of a radiological emergency. Focusing on the campus community within the EPZ, this study investigates individual awareness regarding the potential of a radiological event, the emergency information booklet, and the information provided within the booklet. We use descriptive statistics, frequency distribution, and cross tabulations (contingency tables) to establish awareness levels. Our study determines those participants who read the emergency instructions booklet are prepared to make an informed decision in the event of a radiological incident. We find college affiliation, educational level, university role, and age significantly related to emergency instruction booklet utilization. We also find gender is significantly linked to overall risk perception regarding a radiological event. Findings support previous research regarding women’s higher levels of risk aversion and pessimism involving dangerous new risky technologies and activities like nuclear energy plants. These findings support modifying policy to ensure nuclear facilities assess the efficacy of their warning systems in alerting the public. Furthermore, our findings provide guidance regarding the evaluation of the effectiveness of emergency instruction booklet distribution.